Transposable element and host silencing activity in gigantic genomes - Wang, Jie; Yuan, Liang; Tang, Jiaxing; Liu, Jiongyu; Sun, Cheng; Itgen, Michael W.; Chen, Guiying; Sessions, Stanley K.; Zhang, Guangpu; Mueller, Rachel Lockridge (Frontiers in Cell and Developmental Biology, 2023)
Transposable elements (TEs) and the silencing machinery of their hosts are engaged in a germline arms-race dynamic that shapes TE accumulation and, therefore, genome size. In animal species with extremely large genomes (>10 Gb), TE accumulation has been pushed to the extreme, prompting the question of whether TE silencing also deviates from typical conditions. To address this question, we characterize TE silencing via two pathways -- the piRNA pathway and KRAB-ZFP transcriptional repression -- in the male and female gonads of Ranodon sibiricus, a salamander species with a ~21 Gb genome. We quantify 1) genomic TE diversity, 2) TE expression, and 3) small RNA expression and find a significant relationship between the expression of piRNAs and TEs they target for silencing in both ovaries and testes. We also quantified TE silencing pathway gene expression in R. sibiricus and 14 other vertebrates with genome sizes ranging from 1–130 Gb and find no association between pathway expression and genome size. Taken together, our results reveal that the gigantic R. sibiricus genome includes at least 19 putatively active TE superfamilies, all of which are targeted by the piRNA pathway in proportion to their expression levels, suggesting comprehensive piRNA-mediated silencing. Testes have higher TE expression than ovaries, suggesting that they may contribute more to the species’ high genomic TE load. We posit that apparently conflicting interpretations of TE silencing and genomic gigantism in the literature, as well as the absence of a correlation between TE silencing pathway gene expression and genome size, can be reconciled by considering whether the TE community or the host is currently “on the attack” in the arms race dynamic.